Volatile constituents of Nepeta cataria L., N. glechoma Benth. and N. parviflora M. Bieb. from Hungary - Héthelyi, É. B.; Szabó, L. Gy.; Korány, K. (International Journal of Horticultural Science, 2001)
In the temperate zone live about 150 species of the Nepeta genus. Our investigations covered the examinations of the volatile oil containing species of the genus endemic in Hungary, Nepeta cataria and Nepeta parviflora. Latter is a relict of the ancient steppe-flora and endemic in Hungary as well. Phytochemical examination of the volatile oil containing plant material has also been carried out. Catnip growing in the Botanical Garden of PTE Department of Botany contained 0,67% volatile oil in May and 0,14% in November. Chemical character of the volatile oils were measured by gas chromatography/mass spectrometry and citronellol, citral-A, citral-B and geraniol components were identified. The composition of the oil of November samples shifted towards citronellol (65%). In both samples insecticide and repellent activity bearing compounds (+)-cis-p-menthane-3,8-diol, and (—)-trans-p-menthane-3,8-diol in 2-2.5 and 4-4.5% amount have been found. The catnip sample deriving from Germany contained a small amount of anetol, citronellol, neral, geraniol and geranial (6-13%), and possibly two isomers of nepetalactone in 23-31%.The Nepeta parviflora endemic in the Nagyvolgy valley near Nagykaracsony consisted of the same compounds in the investigated years (1998-2000). Its limonene, methyl chavicol, b-cariophyllene, b-selinene, b-cubebene, davanone, germacrene-D constituents have been identified. In the year 2000 different GC % of these compounds were detected in the different organs of the plants.The closely related species Nepeta cataria var. citriodora contained 83% citral, and the N. glechoma (= Glechoma hederacea) contained 41% a-cubebene, 20% patchoulenol, 7,7% spathulenol respectively. These compounds were identified by gas chromatography and gas chromatography / mass spectrometry.